Effect of Particle Size of a Powder upon the Properties and Microstructure of Boron-modified Fe-Ni-Mo-Cu Sinters - Perek-Nowak, Małgorzata; Majchrowska, Magdalena; Karwan-Baczewska, Joanna; Rosso, Mario (Journal of Casting & Materials Engineering, 2023)
The article discusses the effect of different particle fractions of prealloyed iron powder on the microstructure, density and hardness of sintered material. Each particle fraction (apart from 160–200 µm, which is a trace fraction) was modified with boron, its contents being, respectively, 0.2 wt.%, 0.4 wt.% and 0.6 wt.%. Next, the powder mixtures were pressed under a pressure of 600 MPa, and the final compacts were subject to sintering at 1200°C for 60 min in a hydrogen atmosphere. It was observed that the higher values of density and hardness were found in samples made from finer fractions of powder. A higher homogeneity of the microstructure and the highest degree of compactness was obtained in sinters from powder of 40–56 µm particle size, with 0.4 wt.% boron. Due to the use of small particle fractions of prealloyed powder, a higher degree of compactness in sinters was obtained with lower boron content. Also indicated was which particle fraction of Fe-Ni-Mo-Cu powder should be applied to obtain density in sinters with boron addition equal to almost 100% of the relative density of the analyzed alloy. The presented studies have both scientific and technological aspects.